Methodological approach of Sport and Health for Overweight children (SHOW) intervention study - Bergmann, Gabriel Gustavo (2021)
Prevention and treatment of overweight among children have been a global challenge. A better understanding of different interventions to improve overweight children’s health is needed. This paper describes the methodological approach of Sport and Health for Overweight children (SHOW) study, which investigated the effects of a multicomponent intervention on health markers of overweight children. The SHOW study is a non-randomized clinical trial performed during 16 weeks enrolling 72 overweight children aged eight to 12 years in an intervention (IG = 35) and control group (CG = 37). It is a multicomponent intervention program including generalized sport initiation, health education, and weekly communication between parents and researchers. Besides characterizing the participants’, several health outcomes were analyzed in the SHOW study. Primary outcomes were accelerometer based physical activity and anthropometric indicators of overweight and obesity. Secondary outcomes were made up of cardiometabolic, fitness, behavioral, and psychological health indicators. We hypothesize that the SHOW study improves health outcomes and can be replicated in other settings as well as implemented by public policies.